THE CONCEPT OF DEVELOPMENT OF THE TOURIST VILLAGE AREA (A CASE STUDY ON GUNUNG MASIGIT DESA, KEC. CIPATAT) - Putu Widyaningsih, Niluh; Aulia Hasanah, Annisa; Suprajaka,; Budi Santoso, Anton (International Journal of Psychosocial Rehabilitation, 2020)
Many regions or cities in Indonesia utilize tourism as the spearhead in developing the economy and strengthening regional autonomy. One example is the Gunungmasigit Village area. Gunungmasigit Village is a beautiful and beautiful village located in Cipatat District, West Bandung Regency, West Java. This village is considered to be very strategic because it is in the location area to Guha Pawon and Stone Garden, close to the Padalarang toll access, and also between Cianjur and Cimahi City. Because of its strategic location, it is easy for tourists to visit this village.However, the village of Gunungmasigit can be said to be undeveloped so it needs to explore issues and further information to find out the problem also the solution to the development of this village because it is not impossible, if the accommodation facilities and supported by other infrastructure In this study, data processing uses 3 (Triple) analysis A. After conducting the research, the researcher examines various references to find out the ideal conditions of a Tourism Village so that researchers can find out the appropriate development concepts for Gunungmasigit Village to become a Tourism Village.From the ideal conditions a Tourism Village can be a platform for researchers to develop a good concept for Gunungmasigit Village so that in the future the development of Gunungmasigit Village becomes a Tourism Village that can provide benefits for many parties. These benefits include improving the economy of the local community, preserving the environment and supporting tourism activities in Guha Pawon and Stone Garden. Some of the development concepts offered by the author are the construction of accommodation facilities, the construction of economic facilities for the sale of souvenirs and regional specialties, promotions, cultural villages, and public facilities such as toilets, parks and Kids Camp.